Pengaruh Gaya Hidup terhadap Kesehatan Mental Remaja - Shalahuddin, Muhammad Abdurrahman; Irsyadi, Muhammad Lingga (Neolectura, 2023)
This study aims to explore the relationship between modern lifestyles and adolescent mental health. The technique applied in this study is a qualitative method with a literature study approach with the aim that the information from the research results can be comprehensive. The sources used in this study include journal articles, books, and industry reports related to the influence of lifestyle on adolescents' mental health, all sources were collected with the keywords